Home Book on Sanitation - Merck & Co., New York (1922)
Home Book on Sanitation with high resolution images - Book with useful information on the sanitary care of the household. Shows how to guard against disease germs and insect pests; included “first aid” for cuts, sores and burns, and gives many practical suggestions on related subjects. Also reviews briefly the sanitary care of domestic animals, poultry, etc. - 4th Edition.